SEED BORNE FUNGI OF URDBEAN - A. N. ROY, R. B. SHARMA* and (Indian Phytopathology, 2002)
Seed of urdbeans collected from three localities around Agra and maintained at 30, 60 and 90 per cent RH and room conditions were tested by blotter paper and agar plate methods for the occurrence of seed borne fungi. Only 4 fungi were found to be pathogenic in soil test.